(untitled) (Fiep Bulletin - online, 2012)
Generally, there is a market of fitness trend to the use of customized trainingservices, provided by personal trainers (PTs). People who seek this type of careto develop a personalized program of physical activity (PPAF) do so for various reasons. These may be related to maintaining or improving our physical capabilities, available to more positive results in relation to aesthetics, the need for motivation for the practice of a structured physical activity, either throughtiredness or because they are not accustomed to the routine practice of physical exercise or, they aim for a more effective practice during this type of activity,which translates into the need for safer guidelines (GARAY, SILVA, Beresford,2008).The influence on body image in today’s society leads individuals to a quest for perfection. This increasing commercialization of the body so ingrained in cultureproduces a paradox between the body and artificial beauty, gently adhering to thebody image, body relating to a standard pre-set as a reference for health, quality of life and beauty. Physical activity as a means to develop individual skills and capabilities in both physical, mental and social, has much contributed to this training (GARAY, SILVA, Beresford, 2008).